Effects of Cordyceps Mushroom Powder on Nursery Pig Performance - J. Richert; J. Y. Palencia; M. T. Thayer; C. Chastain; B. Richert; J. L. Nelssen (Kansas Agricultural Experiment Station Research Reports, 2018)
One hundred sixty crossbred pigs (Duroc × (York × Landrace)) weaned at 18.8 d of age and weighing an average of 13.1 lb were used in a 35-day growth trial to evaluateCordycepsmushroom powder as potential alternative to carbadox in nursery pig diets. Pigs were divided by weight, sex, litter, and assigned to body weight (BW) blocks. Within BW blocks, sex ratios were constant in each pen. Each pen within a BW block was randomly assigned a dietary treatment. Growth performance was analyzed using BW, average daily gain (ADG), average daily feed intake (ADFI), and feed conversion as feed-to-gain (F:G). Pigs were blocked by weight with 5 or 6 pigs per pen and there were 6 pens per treatment. There were 5 diets used in the study: a negative diet or a positive control (carbadox, 50 g/ton); 300 or 600 ppm mushroom powder, and a step-down treatment (900, 900, 450, 300, and 150 ppm mushroom powder during weeks 1, 2, 3, 4, and 5, respectively). At various points of the study, pigs fed the 300 ppm and the step-down mushroom powder treatments tended to have improved (P<0.10) growth performance compared with those fed the negative control diet. During Phase 4 of the study, pigs fed carbadox had greater ADG (P<0.02) and improved feed efficiency (P<0.09) over pigs fed the negative control diet. However, overall data showed that there were no statistical differences among treatments (P>0.05). In summary, pigs fed 300 ppm mushroom powder or the step-down treatment showed comparable results to pigs fed carbadox. However, future research is needed under a greater disease pressure to show mushroom powder’s full potential as an alternative to antibiotics.
Keywords: mushroom powder; antimicrobial; antimicrobial alternative; nursery pigs